Shirking, Endogenous Lay-off Rates and the A-cyclicality of the Real Wage - Gerhard Rünstler (Austrian Institute of Economic Research (WIFO), 2009)
The paper extends the Shapiro-Stiglitz (1987) efficiency wage model by endogenising the probability of worker displacement as a function of the change in the firm's employment. This creates counter-cyclical variation in the wage mark-up and thereby generates real wage persistence. A New Keynesian DSGE model equipped with this extension replicates the empirical facts of a very limited response of the real wage to the business cycle together with a lagged hump-shaped response of employment to output.
Keywords: 330; Efficiency wages; shirking; real wage persistence; New Keynesian models; Effizienzlohn; Reallohn; Dynamisches Gleichgewicht; Neoklassische Synthese; Theorie